Ethiopian taxicab drivers: forming an occupational niche in the US Capital. Issue 2 (2nd July 2016) - Chacko, Elizabeth
ABSTRACT: This paper analyzes the relative roles of cultural and structural factors in the emergence and solidification of taxi driving as an ethnic occupational niche among Ethiopian immigrants in the Washington DC metropolitan area within the wider context of globalization and immigrant integration. An ethnic occupational niche is the concentration and specialization of members of an ethnic group in a particular occupational activity. Using data from the US Census Bureau and in-depth interviews with 25 (male) Ethiopian cab drivers and three Ethiopian cab company owners, it examines the factors that affected the entrance of first-generation Ethiopian immigrants in this occupation since the 1980s. This research demonstrates that mixed embeddedness or the interplay of structural factors such as blocked mobility as well as cultural factors such as the strong social networks that exist among Ethiopian immigrants were important in the induction of new immigrants into taxicab driving. The demographic composition of the Washington metropolitan area and policies of the DC Taxicab Commission that allow for fairly easy entry of new drivers in the taxicab business also facilitated the emergence of this occupational niche.